Ruins of Wilderness - Jonsson Buttery, Sanna (2011)
Ruins and derelict places have since long fascinated and attracted humans. With my starting point in the wild vegetation and the spontaneous activities taking place on derelict land and in industrial ruins, I explore with help from the theoretical sociology, what creates not only this fascination but also fear. The purpose of the thesis is to explore and exemplify how the industrial ruin as a place outside the restrictions and control as well as design intentions of modern society can be used as an inspiration in a landscape architecture context. The modern city consists of areas and places with a well defined purpose. A piece of derelict land or a disused building is instead ambiguous, undefined and open for new purposes. However described in negative terms, these places are often perceived as places of mystery and magic. Spaces with structures and systems of order which differ from the conventional systems challenge our perception of reality. They question an order we take for granted, suggesting that there might be other possibilities. This might be unsettling, but also creates a place free from conventions and social rules. The vegetation is an important symbol of the new or alternative order prevailing on derelict land, which contributes to the chaos that invites the spontaneous use of these spaces. This chaos is also the key to the activities that take place here. The lack of order and control invites physical challenges and play without thought of consequences. The derelict space is a setting for adventurous play, flea markets and privacy, but also for parties and other activities beyond the law. The industrial ruins symbolise places where civilisation has failed, which is the reason to the attraction, but also to a feeling of danger. Introducing design features that encourage more conventional outdoor activities, without restraining the existing ones, can be a way of including the industrial ruin in the park structure of the city.